4 - Narrating National Identity. Fiction, Citizenship and the Asian Experience in East Africa*: 10.4314/ad.v28i1.22170 - Kahyana, Danson (Africa Development, 2022)
The paper examines the crucial question of postcolonial identity in East African nation states, with particular reference to the Asian experience in East Africa. It attempts an examination of the conflict between citizenship and descent, par ticularly as regards the identity of East African Asians. It argues that descent and race are considered more important identity markers than citizenship in postcolonial East Africa, a distinction that has continued to frustrate attempts at building a multi-racial/multi-cultural society. Among other factors, the paper traces British colonial practices, for instance, the construction of a three-tiered society where Whites occupied the top seats, the Indians the middle ones and the Africans the lowest, as furthering a complex social structure and exacerbat ing conflict situations. The paper explores the various ways through which citi zenship and descent conflict has affected and influenced, policies and pronounce ments on Asian identity in East Africa.